Minimally invasive versus conventional extracorporeal circulation circuits in patients undergoing coronary artery bypass surgery: a propensity-matched analysis. (October 2019) - Saha, Shekhar; Varghese, Sam; Herr, Mike; Leistner, Marcus; Ulrich, Christian; Niehaus, Heidi; Ahmad, Ammar Al; Baraki, Hassina; Kutschka, Ingo
Objectives: Minimally invasive extracorporeal circulation circuits provide several advantages compared to conventional extracorporeal circulation circuits. We compared the results of a minimally invasive extracorporeal circulation system with those of conventional extracorporeal circulation system, in patients undergoing isolated coronary artery bypass grafting. Methods: We identified 753 consecutive patients who underwent coronary artery bypass grafting at our centre between October 2014 and September 2016. These patients were divided into two groups: a minimally invasive extracorporeal circulation group (M, n = 229) and a conventional extracorporeal circulation group (C, n = 524). Baseline parameters, details of cardiac surgery as well as postoperative complications and outcomes were compared by means of a propensity-matched analysis of 180 matched pairs. Results: The median EuroSCORE II was 1.3%. Transfusion requirement of packed red blood cells (p = 0.002) was lower in Group M compared to conventional extracorporeal circulation systems. There were no differences in hospital mortality or in rates of adverse events between the matched groups. Total in-hospital mortality of the cohort was 1.7%. Conclusion: The use of minimally invasive extracorporeal circulation is associated with a significantly lower use of blood products after isolated coronary revascularisation. There were no differences concerning duration of surgery, complication rates and mortality between the groups. Therefore, the application of minimally invasive extracorporeal circulation systems should be considered as preferred technique in isolated coronary artery bypass grafting procedures.